O trabalho emocional de uma professora de Inglês de escola pública: um olhar crítico para as emoções - Ana Claudia Turcato de Oliveira (2021)
This research investigated the constitution of the emotional labor of a public school English teacher. Some of the objectives of this study were to investigate how the process of emotional labor of an English language teacher is carried out in her professional context; identify what are the factors that form the emotional labor of the teacher-participant and its effects on her subjectivity as an English teacher and, finally, discuss to what extent the emotional labor of the English teacher challenges as hegemonic norms of power that involve teaching the English language. This case study is characterized as qualitative research of an interpretive paradigm, inserted in the field of Applied Linguistics, using post-structuralist critical theories and concepts from other areas of knowledge such as Education and Philosophy. For data generation, this study used narrative interwiews and qualitative data. For data analysis, it was followed the principal of grounded theory (CORBIN; STRAUSS, 1990). Tha data indicate that the teacherparticipant’s emcoional labor is closely related to the conflicts produced between neoliberal discourse and the desire to become a critical teacher, as well as, it was buil on dissent, on the contradiction, in the negotiation of power inherent in the teaching nature. The introduction of this work presents the general and specific objectives that guide its realization, its justification and research questions. Chapter II presents the theoretical framework that guided this study. Chapter III presents the methodological path followed, encompassing the research methodology and techniques, the profile of the participant and the researcher, as well as their context. Chapter IV discusses the results of the analyzes. Finally, the last chapter presentsthe final considerations and suggestions for future studies.